1998
DOI: 10.2337/diacare.21.5.757
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a Diabetes-Specific Quality-of-Life Scale for Patients With Type 1 Diabetes

Abstract: The DSQOLS is a reliable and valid measure of diabetes-specific quality of life. The scale is able to distinguish between patients with different treatment and dietary regimens and to detect social inequities. Use of the DSQOLS for assessment of individual treatment goals as defined by the patients may be helpful to identify motivational deficits and to tailor individual treatment strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
164
0
9

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(179 citation statements)
references
References 32 publications
6
164
0
9
Order By: Relevance
“…The DSQOLS is a reliable and valid measure of quality of life specific for people with type 1 diabetes 13 . It consists of 2 sections: the treatment satisfaction score and the quality of life score.…”
Section: Methodsmentioning
confidence: 99%
“…The DSQOLS is a reliable and valid measure of quality of life specific for people with type 1 diabetes 13 . It consists of 2 sections: the treatment satisfaction score and the quality of life score.…”
Section: Methodsmentioning
confidence: 99%
“…Three full measures and three sub-scales had sufficient face validity to be considered measures of DD:  PAID (Polonsky et al, 1995)  DDS (Polonsky et al, 2005)  Type I Diabetes Distress Scale (T1-DDS) (Fisher, Polonsky, et al, 2014;Fisher et al, 2015)  'Diabetes-specific Well-being' sub-scale of the Well-Being Questionnaire 28 (W-BQ28) (Bradley, 2000;Speight & Bradley, 2002;Speight, Khagram, & Davies, 2012)  'Burdens and Restrictions -Daily Hassles' sub-scale of the Diabetes-specific Quality of Life Scale (DSQoLs-R) (Bott, Muhlhauser, Overmann, & Berger, 1998;Cooke et al, 2013 (Rubin & Peyrot, 2010) captures only worry related to hypo-and hyperglycemia and long-term complications. Some Diabetes Symptom Checklist-Revised (DSC-R) sub-scales (Arbuckle et al, 2009;Grootenhuis, Snoek, Heine, & Bouter, 1994) capture the emotional distress associated with diabetes symptoms.…”
Section: Identification and Selection Of Measuresmentioning
confidence: 99%
“…Improved quality of life has also been demonstrated after intensification of insulin regimens, an effect attributed to patients' greater perceived flexibility in physical activities and diet (99). Quality of life is adversely affected by the presence of comorbid psychiatric disorders and health complications (71,100), as well as physical complaints and worries about the future (95). In addition, research has shown that quality of life is diminished when diabetes-specific health behaviors are associated with a sense of burden (101).…”
Section: Significancementioning
confidence: 99%
“…Quality of life. Diabetes-related quality of life can be reliably measured (95)(96)(97). Studies have shown that quality of life in adults with diabetes is positively affected by increased physical activity and adequate social support (98).…”
Section: Significancementioning
confidence: 99%